Is biological control for earleaf acacia (Acacia auriculiformis) Feasible in the United States?. Issue 12 (1st December 2020) - Minteer, Carey R.; Smith, Melissa C.; Madeira, Paul; Goosem, Christine; Zonneveld, Ryan; Makinson, Jeff; Wheeler, Gregory S.; Purcell, Matthew
ABSTRACT: Earleaf acacia ( Acacia auriculiformis A.Cunn. ex Benth) is a fast-growing, evergreen tree from Australia that was introduced into the United States as an ornamental plant, but it has become a serious plant invader in Florida, USA. Spread of this invasive tree has accelerated in recent years and current control efforts do not meet conservation or land management needs. Our objective was to review and summarize available information to determine if pursuing classical biological control for earleaf acacia is warranted. Feasibility studies such as this identify pitfalls and conflicts before a project begins, increasing the likelihood that biological control efforts will be successful. This review compiles a list of non-target species based on their geographic overlap with the weed invasion and their relatedness to A. auriculiformis. Feasibility is also determined based on other criteria including conflicts of interest and availability of potential biological control agents. We also present a report from our initial explorations for natural enemies in the native range of Australia. Eighty-nine arthropod and one pathogen species have been identified feeding on earleaf acacia in the native range. Several of the arthropods found have the potential to be host specific and impactful. Few potential conflicts of interests were identified. These findings paired with the high-risk assessment for invasion and lack of sustainable and effective control methods, supports our conclusion that earleaf acacia is a promising target for classical biological control.